The Effect of Precursor Chemical Abuse on Criminal Responsibility - Awda, Jalila (Journal of Legal Sciences, 2025)
This research explores the impact of consuming chemical precursors on criminal liability. It begins by examining the nature of the crime of using chemical precursors, starting with the linguistic definition of precursors, followed by the legal and technical meaning of chemical precursors. The study then analyzes the elements constituting the crime of consuming chemical precursors and the resulting effects on criminal responsibility.The findings indicate that the impact of this crime on criminal liability varies in two main scenarios: voluntary consumption and forced or involuntary consumption. In the case of voluntary drug consumption, the legal approach distinguishes between two situations: intoxication with an expectation of committing a crime, and deliberate intoxication with the intention of committing a crime. As for forced or involuntary consumption, this is the only scenario in which Iraqi legislation considers it a ground for exemption from liability. This exemption applies only if the drug use results from an unforeseen event or force majeure. However, if the substance was taken voluntarily and a crime was committed under its influence, the offender is not entitled to an exemption from punishment.